2nd Annual Summit of the Comprehensive Health Research Centre (CHRC) (Karger Publishers, 2022)
The Comprehensive Health Research Center (CHRC) Annual Summit is a meeting that aims to bring together CHRC researchers in a unique opportunity to debate ideas, and current projects, develop relationships and bonds and affirm the CHRC Research Unit as the transactional research unit, clinic, and public health. In this context, works produced by the different research groups, Ph.D. and Master's students, were also presented. The 2nd CHRC Annual Summit took place on two separate days. On November 18, 2021, online sessions were held due to public health restrictions related to the COVID-19 pandemic. The event's second day took place in person on May 13, 2022. On this day, 45 abstracts were presented after a double-blind review process performed by the event Scientific Committee. This Book of Abstracts integrates the 45 abstracts presented at the 2nd CHRC Annual Summit.